2021
DOI: 10.1016/j.clnu.2020.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Body fat percentage prediction in older adults: Agreement between anthropometric equations and DXA

Abstract: Background: It is difficult to measure body fat percentage in clinical settings. Equations using anthropometric measures are more feasible and can be used to estimate body fat. However, there is a need to analyze their accuracy in older adults. Our study aims to validate the use of anthropometric equations to estimate body fat percentage in older men and women. Methods: This study evaluated data from 127 Brazilian individuals aged between 60 and 91 years. Weight, height, skinfold thickness and waist and hip ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…Achamrah et al (32) have suggested that BIA and DXA are interchangeable methods for estimating BF at the population level; nevertheless, at individual level differences were significant. Other studies have reported similar results across categories of BMI, but other authors have suggested that BIA underestimates BF% (30,37).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Achamrah et al (32) have suggested that BIA and DXA are interchangeable methods for estimating BF at the population level; nevertheless, at individual level differences were significant. Other studies have reported similar results across categories of BMI, but other authors have suggested that BIA underestimates BF% (30,37).…”
Section: Discussionmentioning
confidence: 55%
“…The sample size was calculated for a type I error at α = 0.05 and power = 90% (type II error β = 0.10) and an expected Pearson Correlation Coefficient r = 0.40, which is considered a moderate correlation, the sample size obtained was 62. The Pearson Correlation Coefficient is frequently used as part of the evaluation of reliability of body composition equations ( 37 ). The authorities of the facilities visited wished to include as many participants as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Although caution of interpretation must be given because they combined males and females, the mean body weight and fat mass were 77.1 ± 9.1 kg and 26.9 ± 4.1kg, respectively, while our participant weighed 80.9 kg and had a total fat mass of 21.6 kg, indicating that our participant not only is heavier but has a lower fat mass. Furthermore, compared to another study where individuals with an average age of 70 years lost a significant amount of fat mass after 8 weeks of frequent aerobic or resistance exercise compared to the control group who was sedentary and gained fat mass (Irving et al, 2015); such study provides results in alignment to our participant who is older and is also benefiting from being active throughout the whole week by having a noticeably lower body fat percentage than adult males over the age of 60 years (Silveira, Barbosa, Noll, Pinheiro, & de Oliveira, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…Older adults have more body fat percentages (BFP) than their younger counterparts, and there are gender differences in anthropometric measures and BFP. For example, women showed higher values of BMI, subcutaneous fat, and BFP; older men are prone to show more weight and lean mass ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sarcopenia and Obesity have to be measured by using validated methods for measuring body composition, like whole-body Dual-energy X-ray Absorptiometry (DXA), bioelectrical impedance analysis (BIA), Computed Tomography (CT), and Magnetic Resonance Imaging (MRI) to diagnose obesity, sarcopenia, or both of them ( 5 ) DXA evaluates bone mineral density and is considered a method to assess whole-body and regional soft-tissue composition, which provides good data about the total amount of FM and FFM by body segments ( 13 ). BIA is an adequate and low cost method to measure total water and FFM.…”
Section: Methodsmentioning
confidence: 99%